2012
DOI: 10.1371/journal.pone.0035027
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ABC Efflux Transporters in Placenta from Women with Insulin-Managed Diabetes

Abstract: Drug efflux transporters in the placenta can significantly influence the materno-fetal transfer of a diverse array of drugs and other xenobiotics. To determine if clinically important drug efflux transporter expression is altered in pregnancies complicated by gestational diabetes mellitus (GDM-I) or type 1 diabetes mellitus (T1DM-I), we compared the expression of multidrug resistance protein 1 (MDR1), multidrug resistance-associated protein 2 (MRP2) and the breast cancer resistance protein (BCRP) via western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 50 publications
(58 reference statements)
0
23
0
Order By: Relevance
“…Methods for RNA isolation, cDNA synthesis, and quantitative polymerase chain reaction (qPCR) have been described previously (Anger et al, 2012). Briefly, RNA was extracted from ;75 mg of snap-frozen tissue using TriZol reagent (Invitrogen, Carlsbad, CA) and cDNA was synthesized from 2 mg of DNAse I treated RNA using the High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Burlington, ON, Canada) according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods for RNA isolation, cDNA synthesis, and quantitative polymerase chain reaction (qPCR) have been described previously (Anger et al, 2012). Briefly, RNA was extracted from ;75 mg of snap-frozen tissue using TriZol reagent (Invitrogen, Carlsbad, CA) and cDNA was synthesized from 2 mg of DNAse I treated RNA using the High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Burlington, ON, Canada) according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR oligonucleotides were synthesized at The Hospital for Sick Children (DNA Synthesis Centre, Toronto, ON, Canada) and reconstituted in nuclease-free DEPC H 2 O (Table 1). Amplicon sequences were amplified as described elsewhere (Anger et al, 2012). Melt-curve analysis was used to ensure primer specificity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extraction was performed by methods as described previously (29,30) . Briefly, 300 mg of liver tissue were band was determined with the AlphaEaseFC software (Alpha Innotech).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…It also implies that the transport of drugs by ABC transporters across the placenta could be affected and that certain GDM treatments based on these transporters could be less efficient than expected [50]. Anger et al [51] have shown that the placental protein expression of other ABC transporters (MDR1, MRP2, BCRP) is not altered in GDM pregnancies. However, this study has not taken into account the maternal BMI.…”
Section: Dubé Et Almentioning
confidence: 99%